Divorce and gender equity in Muslim personal law of India - Kauser Edappagath (LexisNexis, 2014)
This book focuses on the issue of gender bias in the Muslim law of divorce in India, especially unilateral talaq, and examines the relevant statutory and the Shariat law as interpreted in India. The author has used as sources, the Quranic verses, practices of the Prophet, and judicial pronouncements. In addition the author also relies on newspaper articles and other books quoting various eminent jurists and social commentators. The author also provides empirical data and statistics gathered by him. The book includes a full discussion of the Dissolution of Muslim Marriage Act 1939, the Muslim Personal Law (Shariat) Application Act 1937, the Muslim Women (Protection of Rights on Divorce) Act 1986 and the Maintenance for divorced women under section 125 of the Code of Criminal Procedure 1973. It examines the constitutional validity of unilateral talaq, the harsh reality of life after talaq faced by divorced women, their families, and children. It discusses the reforms in the Muslim Personal Law of other countries such as Egypt, Malaysia and Turkey. It also includes the author’s suggestions for remedial measures to curb gender bias and male domination in the matter of talaq in Muslim Personal Law. This book is first of its kind which seeks to examine in detail the issue of gender equity in the matter of divorce in Muslim personal law of India through three dimensional perspective; legal, sociological and Constitutional, relying on substantive empirical data."